The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s13054-015-0857-1
|View full text |Cite
|
Sign up to set email alerts
|

Strain echocardiography in septic shock – a comparison with systolic and diastolic function parameters, cardiac biomarkers and outcome

Abstract: IntroductionMyocardial dysfunction is a well-known complication in septic shock but its characteristics and frequency remains elusive. Here, we evaluate global longitudinal peak strain (GLPS) of the left ventricle as a diagnostic and prognostic tool in septic shock.MethodsFifty adult patients with septic shock admitted to a general intensive care unit were included. Transthoracic echocardiography was performed on the first day, and repeated during and after ICU stay. Laboratory and clinical data and data on ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 30 publications
7
81
1
4
Order By: Relevance
“…In 60 patients with septic shock, the authors found systolic function impairment in 69% of patients assessed with STE, whereas only 33% patients displayed LVEF alteration [20]. In another cohort of 50 patients with septic shock, the authors also described a preserved LVEF when LV global longitudinal peak strain was altered [21]. These findings were confirmed in 35 patients with septic shock [22].…”
Section: Speckle-tracking In the Intensive Care Unitmentioning
confidence: 84%
“…In 60 patients with septic shock, the authors found systolic function impairment in 69% of patients assessed with STE, whereas only 33% patients displayed LVEF alteration [20]. In another cohort of 50 patients with septic shock, the authors also described a preserved LVEF when LV global longitudinal peak strain was altered [21]. These findings were confirmed in 35 patients with septic shock [22].…”
Section: Speckle-tracking In the Intensive Care Unitmentioning
confidence: 84%
“…Of the 46 studies included in this review, 35 examined the association of brain natriuretic peptides (BNP, NT‐proBNP) with survival in patients with septic shock, presented in Table . The vast majority were prospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…This association was also evaluated by two studies in the setting of an RCT evaluating the use of 20% human albumin plus crystalloids or crystalloids alone in patients with severe sepsis or septic shock . In total, 30 studies, including the two conducted in the setting of the RCT, have found a significant association between elevated levels of brain natriuretic peptides and increased mortality …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations